基于虚拟样机技术的X型放大杆系的优化设计 - 王新智; 姜生元; 吴俊飞; 吴爽 (Jixie chuandong)
The concept of X-mode distance-amplifying rods is presented, which can be applied to the distance-lengthening system of hanging-arm high-voltage wire detection robot. the design principle of the system is illustrated and its key parameters are optimized with virtual prototype technology.